Pengaruh Jumlah Penduduk dan Tingkat Pengangguran terhadap Kemiskinan pada Desa Redang Kecamatan Rengat Barat Kabupaten Indragiri Hulu - Tri Rahayu; Aris Triyono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Poverty is a multidimensional condition that describes the inability of individuals or households to fulfill their basic needs, such as food, shelter, education, and health services caused by low income, unemployment, and high population growth. This study aims to determine the effect of population and unemployment rates on poverty levels in Redang Village, West Rengat District, Indragiri Hulu Regency. The type of research is quantitative. The sample in this study was 37 families. The method of determining the sample was a census. The data collection method used was a questionnaire method. The method used to analyze the data was Instrument Test; Validity Test. Classical Assumption Test; Normality Test, Linearity Test, Multiple Regression Analysis, Multiple Correlation Coefficient (R), Determination Coefficient (R2), f test and t test. The results of the study indicate that Population Number (X1) partially has a positive and significant effect on Poverty in Redang Village, West Rengat District, Indragiri Hulu Regency. The unemployment rate (X2) partially has a positive and significant effect on poverty in Redang Village, West Rengat District, Indragiri Hulu Regency, while population (X1) and unemployment rate (X2) simultaneously have a positive and significant effect on poverty in Redang Village, West Rengat District, Indragiri Hulu Regency.